Strategi Manajemen Sumber Daya Manusia Berbasis Syariah untuk Meningkatkan Kinerja Karyawan di Lembaga Keuangan Syariah dalam Perspektif Al-Quran - Moh Agus Sifa'; Heri Kuncoro Putro; M. Mun'im (Journal of Islamic Banking, 2025)
This article discusses sharia-based human resource management (HR) strategies which aim to improve employee performance in sharia financial institutions. Implementing HR management in accordance with Islamic principles is not only important for sharia compliance, but also for creating an ethical and productive work environment. Through analysis of various strategic elements, including recruitment and selection, training and development, performance appraisal, reward systems, and leadership, this article highlights the importance of integrating sharia values ​​in every aspect of HR management. By referring to verses of the Koran, such as QS. An-Nisa [4]: ​​58 which emphasizes trust and justice, QS. Al-Baqarah [2]: 261 which describes blessings in work, as well as QS. Al-Mulk [67]: 15 which encourages good work ethics, this article shows that the application of these principles can produce employees who are not only competent, but also have integrity. This research implies that sharia-based HR management strategies can make a significant contribution to the performance of sharia financial institutions, as well as their reputation in society.